FAMILY RUN SMEs IN NEPAL AND THEIR APPROACH TO MARKETING - Sanghai, Megha Sanghai (2007)
This exploratory research aims to study the role of marketing and its relevance in small and medium sized family businesses in Nepal by comparing it to the combined review of authors and academicians in the field of SME/ entrepreneurial marketing. Although marketing is a key factor in the survival and development of business ventures, SMEs in Nepal cannot do conventional marketing because of the limitations of resources which are inherent to Nepalese SMEs and also because business owner/ managers in Nepal behave and think differently from conventional marketing decision-making practices that take place in large enterprises. In this context the discussion focuses on the characteristics of the Nepalese SMEs and how they have an impact upon the marketing characteristic within their firm. The key findings with respect to marketing competency in Nepalese SMEs and to what extent formal marketing planning is practiced in these enterprises are analyzed. An examination of eight key marketing approaches indicates that SME/ entrepreneurial marketing differ from traditional marketing theory. Family run SMEs in Nepal tends to be customer-oriented driven by the needs and wants of their customer. They target markets through bottom-up approach where they rely on customer recommendations. Even though they unconsciously follow the marketing mix, they prefer interactive marketing methods. The prefer gathering information through networking. These approaches play to their strengths and represent marketing that is more appropriate in their contexts.